Effectiveness of nurses-led cardiac rehabilitation program among coronary artery disease patients attending a teaching hospital, Bharatpur - Shrestha, Rosy; Rajbanshi, Laxmi; Singh, Jaya Prasad; Shrestha, Kshitiz; Shrestha, Sajeeb (Journal of Chitwan Medical College, 2020)
Background: Cardiac rehabilitation (CR) is a comprehensive secondary prevention program, delivered by multidisciplinary team including nurses. This portion in health care sector is found to be lacking and communication between health care providers and cardiac patients is frequently suboptimal. The aim of this study was to identify the effectiveness of nurse-led cardiac rehabilitation program among coronary artery disease patients attending a teaching hospital in Bharatpur, Nepal. Methods: One group pre-test post-test design was used. Total 85 CAD patients were selected for pre and post-test, baseline information was collected using consecutive sampling technique. The education intervention on CR was developed in Nepali language and distributed to each respondent after pre-test in separate room of OPD of Chitwan medical college and teaching hospital, Bharatpur. After one month of education intervention program, post-test was conducted with same subjects using face to face interview questionnaire using CADE-Q. Data was analyzed using Wilcoxon Rang signed test. Results: Of all 85 respondents, median difference between pre-test was 17 (IQR=14-22) and post-test was 39 (IQR=32-44) which was statistically significant (p=<0.001). The percentage of respondents with non-acceptable level (<50%) of knowledge sharply declined from 96.4% to 11.7% whereas those with acceptable knowledge (≥50%) significantly increased to 3.53% to 88.2% at p value <0.001. Conclusion:The nurse-led educational intervention programme considerably improved the knowledge on Cardiac Rehabilitation among CAD patients. Hence, it is strongly recommended that nurses should be involved in establishing and organizing cardiac rehabilitation programs at each tertiary level hospital in Nepal.